Power Quality Monitoring in a Single-phase Power System - Radil, Tomas (2009)
In this paper, the results obtained using a new method for detection and classification of power quality (PQ) disturbances in single-phase power systems are presented. The method detects transients, waveform distortions and short and long duration disturbances such as sags, swells and interruptions. The proposed method was implemented in a measuring system and used for continuous monitoring of a single-phase power system.